Multi-pulse residual excitation model (MP-PRE) - Shah, Asadullah; Shaikh, Muniba (IIUM Press, 2011)
The Multi-Pulse Residual Excitation (MP-PRE) is a modified version of PRELP. The design of MP-PRE considers that after short term and long term correlations yet some correlation exist over the onset and sudden transitional regions where the energy of the signal is rising. This chapter explains the MP-PRE algorithms ofencoding speech at low bit rates.